Picture Your Nursing Home: Exploring the Sense of Home of Older Residents through Photography. (5th August 2015) - van Hoof, J.; Verhagen, M. M.; Wouters, E. J. M.; Marston, H. R.; Rijnaard, M. D.; Janssen, B. M.
Abstract : The quality of the built environment can impact the quality of life and the sense of home of nursing home residents. This study investigated (1) which factors in the physical and social environment correlate with the sense of home of the residents and (2) which environmental factors are most meaningful. Twelve participants engaged in a qualitative study, in which photography was as a supportive tool for subsequent interviews. The data were analysed based on the six phases by Braun and Clarke. The four themes identified are (1) the physical view; (2) mobility and accessibility; (3) space, place, and personal belongings; and (4) the social environment and activities. A holistic understanding of which features of the built environment are appreciated by the residents can lead to the design and retrofitting of nursing homes that are more in line with personal wishes.